Community Participation When Comparing Academic Text before the Establishment of Regional Regulations in Nabire District - Petrus Tekege (Budapest International Research and Critics University, 2022)
This writing aims to provide an understanding that academic texts are doors or windows, breaths, directions for the formation of regional regulations. For this purpose, the researcher uses normative legal research methods and sociological legal research methods, namely research based on legal sciences, especially constitutional law, which is not only a normative problem but also includes socio-empirical problems, in accordance with the phenomenon and the reality that develops in the Nabire-Papuan community. In an effort to collect data the researchers based on primary data sources and secondary data sources. Based on these data, the writer then analyzed using qualitative methods. Based on research, the results show that there is a regional regulation that begins with the preparation of an academic text made by a certain team without capturing the aspirations of the people who are participatory starting from planning, forming, implementing, monitoring and evaluating so that it results in the community being apathetic and accepting as is every regional regulation formed by the regional government and Nabire Regency DPRD. For this reason, it is important for the formation of regional regulations to first form participatory academic texts which are then inseparable from regional regulations. As a mirror of academic texts, it will be effective for local regulations in their formation. The effectiveness of the enactment of regional regulations is highly dependent on the extent to which the community accepts the enactment of regional regulations.